Predictors of current suicidal ideation in a multi-diagnostic sample of individuals with eating disorders - Alyssa M. Izquierdo; Jillian D. Nelson; Alyssa Daza; Alexandra Gasbarro; Rebecca Hardin; Joanna Marino; Sarah Fischer (Journal of Eating Disorders, 2023)
Abstract Background Individuals with eating disorders (EDs) have high rates of suicidal ideation (SI) and attempts (SA). Fasting, body dissatisfaction, binge eating and purging have been associated with SI in non-clinical samples, individuals with anorexia nervosa or low-weight EDs, and a multi-diagnostic sample. However, few studies have examined how ED symptoms contribute to risk for SI in conjunction with other well-established risk factors, such as nonsuicidal self-injury (NSSI) and past SA. The aim of this study was to examine which ED symptoms contribute unique risk for current SI in a multi-diagnostic, clinical sample when statistically adjusting for gender, NSSI, past SA, and past SI. Methods We conducted a chart review of 166 individuals who presented for ED treatment at an outpatient facility and signed informed consent. Initial intake interviews were coded for the presence versus absence of fasting, fear of weight gain, binge eating, purging, excessive exercise, restriction, body checking, self-weighing, and body dissatisfaction, as well as NSSI, past SA, past SI, and current SI. Results A total of 26.5% of the sample endorsed current SI. In a logistic regression analysis, identifying as male (n = 17) or having a non-binary gender identity (n = 1), the presence of fasting, and past SI were all significantly associated with increased odds of current SI, whereas excessive exercise significantly decreased odds of current SI. Fasting was equally common across all diagnostic groups. Conclusions Future research should establish the temporal relationship between fasting and SI to better inform intervention.